Irish literature since 1990 diverse voices - Brewster, Scott; Parker, Michael 1949- (Manchester Univ. Press, 2009)
This title contains a unique range of international contributors, bringing new perspectives to the study of Irish literature and culture.
Includes index
Keywords: Geschichte 1900-2000; Geschichte 1990-2009; English literature / Irish authors / History and criticism; English literature / 20th century / History and criticism; Irish literature / 20th century / History and criticism; National characteristics, Irish, in literature; English literature -- Irish authors -- History and criticism; English literature -- 20th century -- History and criticism; Irish literature -- 20th century -- History and criticism; Literatur; Ireland / In literature; Irland; Ireland -- In literature; Aufsatzsammlung